Metamorfosis de los dioses y las sacerdotisas andinos en Huamantanga (Canta), siglo XVII - Cajavilca Navarro, Luis (2007)
In Huamantanga, Catholic missionaries and idolatry extirpators destroyed the «guanca» stones that represented Andean gods. All the national and local idols had prophetic powers and their cult consisted in prayers by Andean priestesses.